2016
DOI: 10.2109/jcersj2.15209
|View full text |Cite
|
Sign up to set email alerts
|

Rapid formation of hydroxyapatite layer on polyetheretherketone by vacuum ultraviolet irradiation and microwave heating techniques

Abstract: Rapid formation of hydroxyapatite [Ca 10 (PO 4 ) 6 (OH) 2 ; HAp] layer on the polyetheretherketone (PEEK) substrate was examined by the combined techniques of vacuum ultraviolet (VUV) irradiation and microwave heating. The surface properties of PEEK substrate were modified by the formation of carboxyl group due to the VUV irradiation at room temperature in air, whereas the formation of HAp layer was encouraged by the microwave heating of surface-modified PEEK substrate in the HAp-dissolved solution. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In addition, there are physical treatments that result in various types of surface modifications. Examples include thermal treatments [36,37], glow discharge [73][74][75], ultraviolet [49,[75][76][77], and high-energy low-current DC electron beam [78,79] irradiations, as well as electron cyclotron resonance plasma oxidation [80] and laser [81,82] treatments, which together produce very thin surface layers of the substrate with oxidation and/or partial degradation [49,[73][74][75][76][77][78][79][80][81] or surface texturization [82]. More specifically, the surface of substrates can be coated with an interlayer of another compound [48,67,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] containing special binding agents [99][100][101] be...…”
Section: General Knowledge Terminology and Definitionsmentioning
confidence: 99%
“…In addition, there are physical treatments that result in various types of surface modifications. Examples include thermal treatments [36,37], glow discharge [73][74][75], ultraviolet [49,[75][76][77], and high-energy low-current DC electron beam [78,79] irradiations, as well as electron cyclotron resonance plasma oxidation [80] and laser [81,82] treatments, which together produce very thin surface layers of the substrate with oxidation and/or partial degradation [49,[73][74][75][76][77][78][79][80][81] or surface texturization [82]. More specifically, the surface of substrates can be coated with an interlayer of another compound [48,67,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] containing special binding agents [99][100][101] be...…”
Section: General Knowledge Terminology and Definitionsmentioning
confidence: 99%
“…Various inorganic bioactive materials have been used as coatings to improve the cell affinity and osteointegration of PEEK implants. For instance, Suzuki et al [65] developed a rapid coating technique to deposit HA layer (10 µm) onto PEEK through combined vacuum ultraviolet (VUV) irradiation and microwave heating technique. Lee et al [66] applied a cold spray HA coating on PEEK (see Fig 3a), and animal study showed that the quantity of newly formed bone around HA-coated PEEK was significantly higher than that of the bare PEEK group.…”
Section: Inorganic Coatingsmentioning
confidence: 99%
“…1−9 Therefore, PEEK is widely considered as an alternative to metals in automobiles, aircrafts, biomaterials, and electronics. 2,5,10 Its specific applications include turbine blades, gears, bearings, bumpers, pipes, blankets of vehicles, and aerospace crafts, as well as orthopedic and spinal implants and electronic substrates. In addition, PEEK possesses high processability at a temperature higher than its melting point (ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Poly­(ether ether ketone) (PEEK) has attracted much attention as a superengineering thermoplastic with remarkable mechanical robustness, superior chemical resistance, high thermal stability, low abrasiveness, absence of toxicity, and biological inertness. Therefore, PEEK is widely considered as an alternative to metals in automobiles, aircrafts, biomaterials, and electronics. ,, Its specific applications include turbine blades, gears, bearings, bumpers, pipes, blankets of vehicles, and aerospace crafts, as well as orthopedic and spinal implants and electronic substrates. In addition, PEEK possesses high processability at a temperature higher than its melting point (ca.…”
Section: Introductionmentioning
confidence: 99%